2017
DOI: 10.1021/acs.chemmater.6b03979
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Highly Efficient Thermally Activated Delayed Fluorescence Hosts for Blue Phosphorescent and Fluorescent Organic Light-Emitting Diodes

Abstract: Recently, thermally activated delayed fluorescence (TADF) materials have become the most promising hosts for realizing high-performance phosphorescent and fluorescent organic light-emitting diodes (OLEDs) because of their ability to upconvert triplet excitons to singlet excitons. However, despite a few TADF hosts having been introduced for low energy phosphorescent and fluorescent dopants, developing host materials with TADF properties for blue phosphorescent and TADF OLEDs is still a great challenge to date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 77 publications
2
36
0
Order By: Relevance
“…Whereas the two weak absorption peaks at 328 and 341 nm were assigned as characteristic peak of Cz‐centered n–π* transition. Due to steric hindrance of 2,2′‐dimethylbiphenyl system, there was no CT absorption peak observed at longer wavelength region in the UV–vis absorption spectra . The estimated optical E g of m‐ CBPPO was 3.5 eV (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas the two weak absorption peaks at 328 and 341 nm were assigned as characteristic peak of Cz‐centered n–π* transition. Due to steric hindrance of 2,2′‐dimethylbiphenyl system, there was no CT absorption peak observed at longer wavelength region in the UV–vis absorption spectra . The estimated optical E g of m‐ CBPPO was 3.5 eV (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The EL maximum of 462 nm without any vibrational shoulder peak and a narrow FWHM of 52 nm was observed from the EL spectrum showing high color purity. From the previous reports, it is observed that most blue‐emitting Ir(III) complexes possess vibrational shoulder peak due to larger oscillator strength at longer wavelengths, resulting in a poor color purity in deep‐blue PHOLEDs. From the observed EL spectra, there was no identifiable emission from the host m‐ CBPPO, suggesting the efficient energy transfer from m‐ CBPPO to Ir(cb) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations